Anti-listerial activity of thermophilin 110 and pediocin in fermented milk and whey. (July 2021) - Ceruso, Marina; Liu, Yanhong; Gunther, Nereus W.; Pepe, Tiziana; Anastasio, Aniello; Qi, Phoebe X.; Tomasula, Peggy M.; Renye, John A.
Abstract: Listeria monocytogenes is a pathogenic bacterium responsible for foodborne illness worldwide. Antimicrobial peptides, or bacteriocins, produced by food-grade lactic acid bacteria can serve as preservatives to prevent Listeria 's growth in various foods, including dairy products. This study investigated the anti-listerial activities of bacteriocin-producing lactic acid bacteria, Streptococcus thermophilus B59671, and Lactobacillus plantarum 076. In vitro studies showed that the concentration of pediocin produced by L. plantarum 076 (2560 AU/mL) inhibited the growth of a six-strain cocktail of L. monocytogenes . However, the concentration of thermophilin 110 produced by S. thermophilus B59671 (320 AU/mL) only delayed the growth by ~2 h. Higher concentrations of thermophilin 110 (≥640 AU/mL) suppressed Listeria growth for up to 22 h. Pasteurized skim milk fermented with a co-culture of S. thermophilus B59671 and L. plantarum 076 reduced the number of L. monocytogenes cells by > 4 Log CFU/mL due mainly to the activity of pediocin. The anti-listerial activity was not observed in whey samples collected from pasteurized skim milk fermented with this co-culture but was detected when raw milk was the substrate. Two additional whey preparations, the by-products from commercial bovine and goat raw-milk cheeses, also inhibited Listeria growth and reduced the number of cells following storage at 4 °C for one week. This study showed that a concentrated preparation of thermophilin 110 has potential as an anti-listerial compound. It demonstrated the prospect of using a co-culture of S. thermophilus B59671 and L. plantarum 076 to prevent Listeria contamination in dairy foods. Additionally, results showed that metabolites with antimicrobial activities may be generated during the fermentation of raw milk due to indigenous microflora. Highlights: Thermophililin 110 inhibited growth of Listeria monocytogenes at ≥ 640 AU ml −1 . Listeria counts were reduced by 4 Log in fermented milk containing bacteriocins. Whey recovered from raw milk fermentations inhibited the growth of L. monocytogenes .